Studi Komparasi Antara Kompilasi Hukum Islam Dengan Madzhab Syafi’i Dan Hanafi Tentang Status Anak Sah - Achmad Shofiyulloh (Kampus Akademik Publiser, 2024)
This study aims to harmonize Islamic law with positive law in the Compilation of Islamic Law (KHI) by comparing the Shafi'i and Hanafi schools regarding the concept of legitimate children. This research uses a normative approach in the type of library research, collecting qualitative data through documentation techniques. The results show that the KHI regulates that legitimate children are those born from a valid marriage, although this can cause confusion in lineage. Significant differences can be seen in the determination of the time limit between marriage and child birth between KHI and the Syafi'i and Hanafi schools, as well as their views on children born outside of marriage registration